Dental asymmetry and identification of racial mixture in a post-conquest sample unearthed in the catedral de Pereira, Colombia - Rodríguez-Flórez, Carlos David; Pulgarín, Eliana (Revista Facultad de Odontología Universidad de Antioquia, 2011)
Introduction: Colombia has suffered a continuous process of biological mixture throughout history. Dental analyses have allowed to observe the variation of discontinuous features in the native Indian population and in the contemporary population in Bogotá and Valle del Cauca. These studies show a different and incompatible morphological tendency with the classification of castes preserved since colonial times. The aim of this article is to identify dental variation in a post colonial sample unearthed in the city of Pereira, Colombia and it is directly associated with the biological variation records in early mixed populations of our country. Materials: the sample used in this study corresponds to teeth extracted between columns F2-F4 and F3-G3 of Cathedral Nuestra Señora de la Pobreza, Pereira, Colombia, which apparently belong to collective burials performed in common burial sites during colonial times, belonging to 28 individuals. Methods: non-metric dental traits were observed using the Standard ASUDAS and other authors, in total 165 non metric traits were examined. An χ2 distribution test was used to identify significant differences. Results: 31 traits showed statistical significant differences on both sides of the arches. Conclusions: they were young mixed children descendents from couples with Caucasoid- Amerindian racial profiles. The percentage obtained in this study corresponds only to the expression of partial mixing since all the hereditary characteristics were strictly dental.